The Effect of Accounting Profit, Retained Earnings and Operating Cash Flow on Cash Dividends (Empirical Study on Sub-Sector Manufacturing Companies Food and Beverages Listed on The Indonesia Stock Exchange Period 2018-2022) - Nuraisyah, Nuraisyah; Mubarak, Husni (Politeknik Negeri Bengkalis, 2024)
This study aims to identify the effect of accounting profit, retained earnings and operating cash flow on cash dividends. The population in this study were all food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2018-2022 period. The research period was carried out for 5 years. The sampling technique used was purposive sampling technique with a sample of 12 companies obtaining a sample of 60 based on certain criteria. The analysis method for this research uses multiple linear regression with the help of SPSS Version 25. The results of this study indicate that partially accounting profit has a positive effect on cash dividends, retained earnings have a negative effect on cash dividends and operating cash flow has no effect on cash dividends. Simultaneously accounting profit, retained earnings and operating cash flow have a significant effect on cash dividends.